2021
DOI: 10.1192/j.eurpsy.2021.2214
|View full text |Cite
|
Sign up to set email alerts
|

How is COVID-19 affecting patients with obsessive–compulsive disorder? A longitudinal study on the initial phase of the pandemic in a Spanish cohort

Abstract: Background: Although the consequences of the COVID-19 pandemic on emotional health are evident, little is known about its impact on patients with obsessive-compulsive disorder (OCD).Methods: 127 patients with OCD who attended a specialist OCD Clinic in Barcelona, Spain, were assessed by phone from April 27 to May 25, 2020, during the early phase of the pandemic, using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) and a structured interview that collected clinical and sociodemographic information. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 30 publications
7
56
0
1
Order By: Relevance
“…Fear of infection, germs, contamination, and cleaning compulsions are some of the most frequently reported OCD symptoms ( Abramowitz et al, 2010 , Cordeiro et al, 2015 ). Recent empirical evidence suggests that the onset of the COVID-19 pandemic has been a significant stressor for individuals with OCD and has been associated with increased severity of obsessions and compulsions, particularly, for those with pre-existing contamination symptoms ( Alonso et al, 2021 , Benatti et al, 2020 , Guzick et al, 2021 , Jelinek et al, 2021 , Tanir et al, 2020 ). For instance, several studies have shown increased frequency of obsessions, time spent on compulsive behaviors, higher reported distress and lower perceived controllability over OCD symptoms in OCD patients during the pandemic ( Alonso et al, 2021 , Jelinek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fear of infection, germs, contamination, and cleaning compulsions are some of the most frequently reported OCD symptoms ( Abramowitz et al, 2010 , Cordeiro et al, 2015 ). Recent empirical evidence suggests that the onset of the COVID-19 pandemic has been a significant stressor for individuals with OCD and has been associated with increased severity of obsessions and compulsions, particularly, for those with pre-existing contamination symptoms ( Alonso et al, 2021 , Benatti et al, 2020 , Guzick et al, 2021 , Jelinek et al, 2021 , Tanir et al, 2020 ). For instance, several studies have shown increased frequency of obsessions, time spent on compulsive behaviors, higher reported distress and lower perceived controllability over OCD symptoms in OCD patients during the pandemic ( Alonso et al, 2021 , Jelinek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most [but not all ( Davide et al, 2020 ; Khosravani et al, 2021 )] clinical studies that did not employ a quantitative assessment of SLEs related to the pandemic have also found that the majority of OCD outpatients did not display short-term (<1 year) symptoms deterioration ( Alonso et al, 2021 ; Benatti et al, 2020 ; Carmi et al, 2021 ; Chakraborty and Karmakar, 2020 ; Matsunaga et al, 2020 ; Schwartz-Lifshitz et al, 2020 ; Sharma et al, 2021 ). This is in line with the assumption that people with a previous mental disorder may have more resources to deal with the pandemic, since they chronically experience fear and isolation states in their daily lives ( Florence et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Carmi et al, 2021 ; Davide et al, 2020 )], and to the geographical origin of the study [countries have differed in their lockdown policies and death rates during the pandemic (e.g. Alonso et al, 2021 ; Højgaard et al, 2021 ; Matsunaga et al, 2020 )]. For instance, compared to other regions in the world, Brazil has been known for its inconsistent lockdown policies and, at different moments in the pandemic, one of the world's fastest growing COVID-19 infection rates ( de Souza et al, 2020 )).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that people with OCD suffered a substantial impact with the current pandemic ( French and Lyne, 2020 ; Jelinek et al, 2020 ; Alonso et al, 2021 ), especially those with contamination-related and washing-related compulsions ( Fontenelle and Miguel, 2020 ). A recent study by Alonso et al (2021) during the initial (and acute) stage of the lockdown in Spain showed that OCD patients experienced symptoms worsening and the appearance of COVID-19-related obsessions (e.g., fear of getting infected by SARS-CoV2). However, it was also stressed that the majority of the OCD patients (as compared to healthy controls) showed adaptive coping strategies with the emotional distress caused by the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was also stressed that the majority of the OCD patients (as compared to healthy controls) showed adaptive coping strategies with the emotional distress caused by the lockdown. This impact may have been moderated by several socio-emotional variables, such as resilience strategies involving online communication with relatives, physical self-care and adequate financial state ( Alonso et al, 2021 ). It is therefore important to identify those patients at higher risk of worsening symptomatology during the pandemic in order to improve the support provided for such patients in a similar situation in the future.…”
Section: Introductionmentioning
confidence: 99%